Phytochemical analysis screening, antioxidant activity and preparation of lotion containing propolis extract from stingless bee - Meechai, Imron; Yuerae, Darunee; Chelong, Isma-ae (Recent Science and Technology, 2021)
The purpose of this research was to analyze the phytochemical screening, antioxidant activity and preparation of lotion containing propolis extract from Stingless bees (Geniotrigona thoracica). The propolis was extracted by reflux method with ethanolic extraction for 1 hour. The ethanol extract (EE) of propolis was extracted with hexane and ethyl acetate, respectively, to obtain hexane extract (HE), ethyl acetate extract (EAE) and residue extract (RE). In the phytochemical screening analysis, chemical composition of all extracts included flavonoid, coumarin, saponin, terpenoid, steroid and cardiac glycoside. The result of antioxidant activity showed that EAE had the highest antioxidant activity with the IC50 value at 262.43 µg/mL and total phenolic content at 60.13 mg GAE/g extract. Therefore, the EAE was selected to prepare the lotion. Five formulations (F1-F5) of lotion were prepared with various concentrations of propolis extract. All of lotion formula represented the oil in water (O/W) type of emulsion and the range of pH with 6.12-6.50. The F3 lotion yielded better result than other formula which revealed homogeneity emulsion and stability temperature changes at temperature of 30±2 and 4±2 °C for 7, 15 and 30 days. However, the efficiency of antioxidant activity decreased after being stored for a long time. Based on this research, the data might be further used for the development of lotion formulations containing propolis extract in cosmetic industry.